Night will fall [videorecording (DVD)] - Bonham Carter, Helena, 1966-; Britton, Jasper
The story of the incredible efforts made by British cameramen to film and document the unbelievable atrocities the Allies encountered during the Liberation of the German Concentration camps in 1945 at the end of World War II.